2016
DOI: 10.1016/j.neurobiolaging.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of calorie restriction in middle-aged male rats attenuates aging-related motoric decline and bradykinesia without increased striatal dopamine

Abstract: Aging-related bradykinesia affects ~15% of those reaching age 65 and 50% of those reaching their 80s. Given this high risk and lack of pharmacological therapeutics, non-invasive lifestyle strategies should be identified to diminish its risk and identify the neurobiological targets to reduce aging-related bradykinesia. Early-life, long-term calorie restriction (CR) attenuates aging-related bradykinesia in rodents. Here, we addressed whether CR initiation at middle age could attenuate aging-related bradykinesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 63 publications
9
36
0
Order By: Relevance
“…Therefore, the protective effects of CR on redox homeostasis in aging brain seem to be preserved when CR is inducted around the middle adulthood. These findings are very consistent with the previous research in the same age group of mice, where functional loss was documented (Salvatore et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, the protective effects of CR on redox homeostasis in aging brain seem to be preserved when CR is inducted around the middle adulthood. These findings are very consistent with the previous research in the same age group of mice, where functional loss was documented (Salvatore et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are very consistent with the previous research in the same age group of mice, where functional loss was documented (Salvatore et al, 2016(Salvatore et al, , 2017.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Singh et al introduced an IF regimen (EOD) to 21-mo old male Wistar rats for 3 months and noted significant improvements in motor performance (rotarod test) and cognition (MWM) (Singh et al, 2012). Salvatore et al reported that 30% CR introduced to F344BNF1 rats at 12 mo of age significantly attenuated the longitudinal decline in locomotor behavior measured in the open field (Salvatore et al, 2016). …”
Section: At What Age Does Cr No Longer Produce Benefits?mentioning
confidence: 99%